Responsible gambling through a motivational telephone intervention to high-risk gamblers – An evaluation of user satisfaction and subjective intervention effects - Håkansson, Anders; Franklin, Katja; Dahlström, Maria; Lyckberg, Axel (Frontiers in Psychology, 2022)
Background and aims Problem gambling causes major social and psychiatric consequences, and there is need to develop feasible harm-reducing or therapeutic interventions. It has been suggested that gambling operators with responsible gambling intentions can intervene in order to identify and help reduce the harm in problem gamblers. However, user satisfaction, and the risk of negative reactions and gamblers’ transfer to other operators, rarely have been explored scientifically. Methods This is a retrospective survey study of gamblers reached by a motivational, telephone intervention by the Swedish state-owned gambling operator (Svenska Spel), addressing gamblers with indicators of high-risk gambling practices (n = 197). Surveys were answered approximately 10 days after the intervention. Results Thirty-seven percent perceived their gambling to have decreased due to the intervention, whereas 7% perceived their gambling instead had increased. A large majority (80%) reported a subjective favorable experience from the intervention. Forty percent reported gambling on other operators than Svenska Spel after the intervention, but only 7% gambled on a new operator following the intervention. Conclusion Survey data in gamblers reached with a motivational telephone intervention present mainly promising findings, and should be replicated in future studies in larger samples. The main findings display an overwhelmingly favorable subjective experience, and a limited risk of gamblers migrating to other operators.